Enhancing Bajra (Pennisetum Glaucum L.) Growth And Yield With Combined Organic And Inorganic Fertilizers (International Journal of Environmental Sciences, 2025)
A field experiment entitled “Enhancing bajra (Pennisetum glaucum L.) growth and yield with combined organic and inorganic fertilizers” was conducted during rabi season of 2024 at Research Farm, Guru Kashi University, Talwandi Sabo, Bathinda (Punjab). The experiment was conducted in Randomized Complete Block Design (RCBD) with one control and 7 treatments with three replications. The treatments consisted of T1: Control (No fertilizer), T2: 75% of Recommended dose of nitrogen (RDN), T3: 75% RDN + Farmyard manure (FYM) @ 5 t/ha, T4: 75% RDN + FYM @ 5 t/ha + ZnSO4 @ 16 kg ha-1, T5: 75% RDN + Vermicompost @ 2 t/ha, T6: 75% RDN + Vermicompost @ 2 t/ha + ZnSO4 @ 16 kg ha-1, T7: 100% RDN, T8: 100% RDN + FYM @ 5 t/ha, T9: 100% RDN + FYM @ 5 t/ha + ZnSO4 @ 16 kg ha-1, T10: 100% RDN + Vermicompost @ 2 t/ha, T11: 75% RDN + Vermicompost @ 2 t/ha + ZnSO4 @ 16 kg ha-1. Results revealed that significant improvements in plant height, dry matter accumulation, number of tillers, ear length, and yield components under integrated nutrient treatments. The combination of 100% RDN + FYM @ 5 t/ha + ZnSO₄ @ 16 kg/ha (T9) and 100% RDN + Vermicompost @ 2 t/ha + ZnSO₄ @ 16 kg/ha (T11) recorded the highest grain yield, stover yield and nitrogen content in both grain and stover. These treatments also provided the highest gross returns (₹83,596 and ₹78,330/ha, respectively), net returns (₹51,272 and ₹44,940/ha), and benefit-cost ratios (1.58 and 1.34, respectively). The findings underscore the synergistic effect of combining inorganic fertilizers with organic manures and zinc in enhancing crop productivity, profitability, and soil nutrient uptake. Integrated nutrient management practices, particularly the inclusion of vermicompost and ZnSO₄, hold promise for sustainable bajra cultivation under semi-arid conditions.